The Influence of Discipline and Motivation on Employee Performance: Empirical Study from PT. Food and Beverages Indonesia, QBig BSD City Branch, Tangerang - Mogi, Agustina (Manunggal Halim Jaya, 2025)
This study examines the influence of discipline and motivation on team member performance at PT. Foods Beverages Indonesia, QBig BSD City Branch. A quantitative approach with a descriptive-associative method is employed. The population consists of all 50 employees at the company, and the sample is determined using a saturated sampling technique, which includes the entire population. Data are collected through questionnaires and analyzed using multiple linear regression. The results indicate that discipline and motivation significantly and positively affect team member performance, with discipline having a more substantial influence. This suggests that employees who adhere to workplace rules and are motivated tend to demonstrate higher performance levels. These findings highlight the importance of maintaining team member discipline and enhancing motivation to achieve optimal organizational goals. The study provides valuable insights for management in formulating effective strategies to improve workforce productivity.